Batch sugar production from sweet sorghum bagasse using Trichoderma reesei. Issue 1 (1st July 2022) - Syadiah, E A; Syamsu, K; Haditjaroko, L; Riska,
Abstract: Sweet sorghum bagasse (SSB) is the dregs of the sweet sorghum plant. SSB is potential lignocellulosic biomass for bioethanol production. SSB cellulose, hemicellulose, and lignin content is 30-40%, 20-30%, and 25-30%, respectively. Previously SSB has been used as animal feed and has not been utilized optimally. Sweet sorghum bagasse has a high content of cellulose. Cellulose biomass can be hydrolyzed by cellulase to produce sugar. The amount of sugar from cellulose hydrolysis will affect bioethanol production. Cultivation was carried out using a batch system for 84 hours. The objectives of this study were to analyze the characteristic of sweet sorghum bagasse, find the pattern of Trichoderma reesei growth, and determine the highest sugar production during cultivation. The method for cultivation of Trichoderma reesei was carried out to determine the microbial growth curve and find the higher sugar production time using a bioreactor. The parameters cultivation process were used to identify the pattern of growth and the required time for producing the highest sugar production. Sweet sorghum bagasse has 48.65 ± 0.02% cellulose, 17.63±0.02% hemicellulose, and 7.47±0.01% lignin. Sweet sorghum bagasse is a potential substrate for bioethanol production. The highest sugar concentration was found at 36 th hours, which was 10.90 g L −1 .